Knowledge and perception of sexually-transmitted diseases of science and non-science undergraduate students in a public university in Malaysia - Lam, Tanya Szee Ee (2021)
Sexually Transmitted Disease s (STDs are amo n g the signi ficant public he al th challenge that can lead to serious complications if left untreated . STDs are most common in persons aged 25 and younger regardless of male or female gender, which is also the adolescent group or undergradua te stud en ts age r ange in thi s study. STDs exa cerbat e the prob lems in he alth sector because directly associated with individual behavior and social issue. Knowledge of STDs is crucial for adolescent to practice appropriate behavio rs that can prevent them fr om cont ra cting S T Ds. However , a knowledgeable adole s cent may not guaran tee that they will have the right perception towards the prevention of STDs , such as proper way to use condom consistently will be followed. Some adolescent even think that s exually tra nsmitte d disease s are not da ngerous because t hey ca n be cured That is the reason why this study were carried in order to assess the knowledge and perception regarding to STDs among undergraduate students. The objective of this study was to determine the level of knowle d g e and perception on sexually tran smitted di seases among science and non science undergraduate students in Universiti Putra Malaysia. This cross sectional study was carried out at Faculty of Modern Languages and Com municat io n Universiti Putra Mal aysia an d Faculty o f Me dicine and Health Sciences Universiti Putra Malaysia. P urpos ive sampling with probability proportionate to size was employed in this study to select 2 faculties out of 16 faculties from Universiti Put ra Mala ys ia The sample size was 120 a nd simp le ran dom sampling technique was conducted to select the participants Data was obtained using questionnaire which was modified, pretested and validated for this study. Data of this study was collected within March and June 2017 using self administered quest ionn aire s Knowledge and perception level on STDs questionnaire of respondents was assessed using English Malay bilingual which had been translated and validated validated. Data analysis was carri ed out using IBM SPSS v ersion 25 . Descriptive a naly ses of th the particarticip ants were collected as frequency, mean, median, and percentage. Logistic regression analysis were applied as inferential statistics for determining predictors of knowledge and perception of STDs, as well as ch i squar square test were used. Pa rticipatrticipation ra te was 98.398.3% for all faculties combined. Among 118 of the students who participated in this study, m ajority (66.1%) of the students were aged 17 to 21 years old while the remaining (33.9%) were aged 22 to 26 yea years old with the mean (SD) age of the re respon de nts of 21.42 ±2.243 2.243. Most of the respondents were female (63.6%) and Malays (57.6%) 57.6%). Majority (68.6%) of the respondents were from semester 1 to 3 and from rural locality (63.6%). Majority (75.4%) of the students obtained STDs knowledge from the internet. 56.8% of the respondents had good knowledge, while 43.2% had poor knowledge. The overall mean (SD) knowledge score for correctly answered questions were 33.11 (±7.413)7.413). 78.3% of respondents from science faculty scored good knowledge while only 34.5% of the respondents from non-science faculty had good knowledge. The comparison of the overall mean knowledge between both groups demonstrated that science undergraduate students had good knowledge level (66.89%) regarding STDs while the non-science undergraduate student had poor knowledge level (46.52%). 66.9% of the respondents possessed positive perception, 33.1% had negative perception. The mean (SD) perception score of the undergraduate students were 12.19 (±2.271). Logistic regression revealed that the knowledge level of student was influenced by their age (AOR= 1.831, 95% CI= 1.276 – 2.544, p-value= 0.003) while faculty (AOR =1.763, 95% CI= 1.287 – 2.365, p value= 0.004) was a significant predictor for perception level. The logistic regression analysis using knowledge level as independent variable demonstrated that respondents knowledge level was very strong predictor for perception level in this study (AOR= 2.865, 95% CI= 2.284 – 3.657, p= 0.001). In conclusion, the study reflects that there is overa overall lo w know ledge level on ST STDs among the non -science undergraduate student group and good knowledge level among the science undergraduate students . Even though there is slightly higher knowledge level am ong stu stude nts of science backg round but they do not implem implement a right perception towards STDs, so as the arts stream students. Most of the stud ents answ ered tha that they were not worried at all if they contracting an STDs. Probably due to they thinking most of the ST STDs can be cured. It is important to implement cont continuou s STDs prevention intervention program to provide the right perception and incre ase the l evel of kn owle dge on STDs especially among adolescent group. It is also recommended that further research should be carried out to det ermine if there is any diffe difference of knowledge and perception of STDs between adolescent from rural and central a reas of Malaysia.